2017
DOI: 10.1016/j.ydbio.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic mosaic deletion of APP results in displaced Reelin-expressing cells in the cerebral cortex

Abstract: It is widely accepted that amyloid precursor protein (APP) plays a central role in the pathogenesis of Alzheimer’s disease. In addition, APP has been proposed to have functions in numerous biological processes including neuronal proliferation, differentiation, migration, axon guidance, and neurite outgrowth, as well as in synapse formation and function. However, germline knockout of APP yields relatively subtle phenotypes, and brain development appears grossly normal. This is thought to be due in part to funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…With regard to the protection of LTP upon ablation of APP, it is 325 important to emphasize the robust nature and generalizability of this phenomenon. We 326 observed the same protection using two different APP KO mouse lines (Zheng et al, 327 1995;Callahan et al, 2017) and extracts from 3 different AD brains. In all cases AD 328 extracts blocked LTP in an Aβ-dependent manner when applied to wild type mouse 329 brain slices, but the same AD extracts had no effect on LTP elicited from APP KO slices.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…With regard to the protection of LTP upon ablation of APP, it is 325 important to emphasize the robust nature and generalizability of this phenomenon. We 326 observed the same protection using two different APP KO mouse lines (Zheng et al, 327 1995;Callahan et al, 2017) and extracts from 3 different AD brains. In all cases AD 328 extracts blocked LTP in an Aβ-dependent manner when applied to wild type mouse 329 brain slices, but the same AD extracts had no effect on LTP elicited from APP KO slices.…”
mentioning
confidence: 53%
“…Wild type (WT) C57BL/6 mice were 473 purchased from Jackson Labs (Bar Harbor, ME). APP KO mice on a C57BL/6 474 background and littermate WT controls were obtained from the Young-Pearse lab 475(Callahan et al, 2017). A second line of APP KO mice were purchased from the 476 Jackson Laboratory (APP tm1Dbo /J,The Jackson Laboratory, Bar Harbor, ME)(Zheng et 477 al.…”
mentioning
confidence: 99%
“…All animal experiments were conducted according to the KU Leuven ethical guidelines and approved by the KU Leuven Committee on Animal Care. Generation of the App NL-G-F mice, Bace1 flox/flox , App KO, and Aplp2 −/− App flox/flox mice were described previously [2,15,18,23]. GAD2Cre mice were obtained from Jackson Laboratory (Jax 010802).…”
Section: Animalsmentioning
confidence: 99%
“…To address directly whether EC-derived APP controls NSC number in vivo, we bred App flox/flox mice (Callahan et al, 2017) with an ECspecific Cre driver, Tie2-Cre (Kisanuki et al, 2001), and an NSC/ astrocyte-specific Cre driver, GFAP-Cre (Zhuo et al, 2001) ;GFAP-Cre mice, respectively. As seen in the conventional App null mutants, more BrdU + label-retaining NSCs were detected in the SVZ of App flox/flox ;Tie2-Cre mice (Fig.…”
Section: App Negatively Regulates the Svz-nsc Number In Vivo In A Nonmentioning
confidence: 99%
“…C57BL/6 mice (The Jackson Laboratory), App mutants (Zheng et al, 1995) (The Jackson Laboratory), App flox/flox mutants (Callahan et al, 2017), Tie2-Cre mice (Kisanuki et al, 2001), GFAP-Cre mice (Zhuo et al, 2001) (The Jackson Laboratory), and Flk1-GFP BAC Tg mice (Ishitobi et al, 2010) have been reported elsewhere. All experiments were carried out according to the guidelines approved by the National Heart, Lung, and Blood Institute Animal Care and Use Committee.…”
Section: Animalsmentioning
confidence: 99%